2004
DOI: 10.1161/01.cir.0000143102.38256.de
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prediction of Fatal Myocardial Infarction Using the Ankle Brachial Index in Addition to Conventional Risk Factors

Abstract: Background-Prediction of major cardiovascular and cerebrovascular events using conventional risk factor models is limited. Noninvasive measures of subclinical atherosclerosis such as the ankle brachial index (ABI) could improve risk prediction and provide more focused primary prevention strategies. We wished to determine the added value of a low ABI in the prediction of long-term risk of cardiovascular and cerebrovascular events and death. Methods and Results-In 1988, 1592 men and women 55 to 74 years of age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
107
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 20 publications
12
107
0
2
Order By: Relevance
“…An ankle-brachial index (ABI) <1.00 is therefore abnormal, although a cut off <0.90 or <0.95 has greater specificity and is used to make the diagnosis of peripheral arterial disease (PAD) in the clinical setting. ABI is a simple, noninvasive method used to assess the presence and extent of PAD [2], and prospective studies have shown that a low ABI predicts fatal and non fatal coronary heart disease (CHD) and all cause mortality [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…An ankle-brachial index (ABI) <1.00 is therefore abnormal, although a cut off <0.90 or <0.95 has greater specificity and is used to make the diagnosis of peripheral arterial disease (PAD) in the clinical setting. ABI is a simple, noninvasive method used to assess the presence and extent of PAD [2], and prospective studies have shown that a low ABI predicts fatal and non fatal coronary heart disease (CHD) and all cause mortality [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although some have recently proposed to screen non invasively in a systematic way men aged 45-75 and women aged 55-75 for subclinical atherosclerosis [28], screening of subclinical atherosclerosis on a population-wide basis should be discouraged [18]. As expected, prevalence of PAD in this selected sample of asymptomatic subjects referred to a Lipid Clinic for CV risk stratification is slightly higher than that reported in population-based surveys [15], [29] and [30], but in keeping with that reported in individuals with diabetes within population-based studies [31]. Although the sample investigated was derived from a single Lipid Clinic in northern Italy, use of the SCORE model should allow an easy comparison with other primary prevention settings of care within and outside our country.…”
Section: Discussionmentioning
confidence: 62%
“…Low ABI values were originally used to identify PAD; however they have subsequently been shown to be an accurate and reliable marker of generalized atherosclerosis and increased risk of CV morbidity and mortality [10], [11] and [12]. Moreover, it has been shown that a low ABI is better at predicting risk of future cardiovascular and cerebrovascular events than conventional risk factors alone [26], and that addition of the ABI significantly improves prediction of CHD mortality over and above conventional risk factors [15]. Although there is yet no evidence that better risk prediction through ABI measurement may translate into reduced incidence of CV events or longer survival, it is reasonable to infer that aggressive treatment for higher risk patients identified by low ABI values irrespective of conventional risk prediction might provide additional benefit in primary prevention of CV events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low values of ABI (o0.95) signal advanced peripheral artery disease and significantly elevated risk of a major cardiovascular disease (CVD) event. [1][2][3][4][5][6][7] Stenotic changes leading to abnormally low ABI are, however, relatively rare in middle-aged persons. 4,5 Furthermore, also elevated ABI (41.40) or high ABP may be associated with increased risk, although the literature is somewhat conflicting.…”
Section: Introductionmentioning
confidence: 99%